2005
DOI: 10.1158/1078-0432.ccr-04-2480
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Staging of Preinvasive Lesions and Occult Lung Cancer in the Central Airways with 18F-Fluorodeoxyglucose Positron Emission Tomography: A Pilot Study

Abstract: Purpose: To evaluate the role of 18 F-fluorodeoxyglucose positron emission tomography (FDG-PET) in radiologically occult preinvasive lesions and lung cancer in the central airways. Experimental Design:Twenty-two patients with 24 preinvasive lesions and early squamous cell cancer (SCC) being occult on high-resolution computed tomography were studied. All lesions were diagnosed based on histology sampled using autofluorescence bronchoscopy. FDG-PET findings were correlated with WHO histologic classification. FDG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Therefore, virtual PET/CT-bronchoscopy will improve diagnostic accuracy in the diagnosis of endotracheal and endobronchial diseases. This is also supported by Pasic et al [18], who suggested that 18 F-FDG PET might be useful for the evaluation of early central airway lung cancer that cannot be visualized with highresolution CT. 18 F-FDG PET imaging has become an accepted and valuable diagnostic imaging tool for patients with cancer. Kamel et al [19] reported that 18 F-FDG PET has a major impact on the management of treatment for patients with small cell lung cancer (SCLC).…”
Section: Discussionsupporting
confidence: 56%
“…Therefore, virtual PET/CT-bronchoscopy will improve diagnostic accuracy in the diagnosis of endotracheal and endobronchial diseases. This is also supported by Pasic et al [18], who suggested that 18 F-FDG PET might be useful for the evaluation of early central airway lung cancer that cannot be visualized with highresolution CT. 18 F-FDG PET imaging has become an accepted and valuable diagnostic imaging tool for patients with cancer. Kamel et al [19] reported that 18 F-FDG PET has a major impact on the management of treatment for patients with small cell lung cancer (SCLC).…”
Section: Discussionsupporting
confidence: 56%
“…However, most of these studies have focused on solitary pulmonary nodules (SPN) or evaluated the FDG uptake of the malignant lesion itself only. Although there have been a few studies on the FDG uptake in evaluation of central airway lesions [28][29][30][31][32][33], to our knowledge, there have been no reports evaluating the FDG uptake pattern at the obstruction site in patients with endobronchial lesions with distal atelectasis.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective series of 20 PET-negative lesions of less than 1 cm at CT, Nomori et al [42 ]reported 8 (40%) malignant tumours, while in 64 non-small cell lung cancers of 2 cm or less, Port et al [43 ]observed 29 (45%) false-negative results, mostly in BACs. On the other hand, a pilot study on 22 patients showed promising results with preinvasive lesions and occult cancer of central airways with an overall accuracy of 79% [44]. …”
Section: Role Of Pet In Detection Of Early Lung Cancermentioning
confidence: 99%